Enhancing Official Statistics Data Dissemination using Google Firebase Platform on Mobile Application: A User-Centered Design Approach - Wisma Eka Nurcahyanti (Politeknik Statistika STIS, 2021)
The dissemination of official statistics as publicly available information has been mandated in the United Nations Fundamental Principles of Official Statistics (UNFPOS) to be highly accessible to all users. Recently, with an increasing volume of data and public demand, National Statistical Offices (NSO) including Statistics Indonesia (BPS) are being challenged to provide accurate, excellent-quality, and user-friendly information. In this paper, we introduce our attempts to enhance the official statistics data dissemination by developing an Android-based mobile application using a User-Centered Design (UCD) approach to meet the requirement of specifically targeted users. Google Firebase platform is utilized to improve the administrator-level usability in updating the disseminated information. The proposed mobile application is launched at BPS-Statistics Madiun Municipality, East Java Province called Batu Cadas (an acronym for BAca TUjuh CAtatan DAta Statistik). Further evaluations using Black-Box functionality testing, System Usability Scale, and specific needs comparison conclude that the proposed mobile application is sufficient to cover the gap between user needs and the currently existing applications.